Exploring faculty experiences with generative artificial intelligence tools integration in second language curricula in Chinese higher education - Javed Iqbal; Vafa Asgarova; Zarqa Farooq Hashmi; Berty Nsolly Ngajie; Muhammad Zaheer Asghar; Hanna Järvenoja (Discover Computing)
Abstract The current study investigates how faculty members in Chinese universities are navigating the integration of generative artificial intelligence tools into second language curricula, focusing on specific pedagogical and institutional challenges. Using an exploratory sequential mixed-method approach (N = 776), we examined how faculty perceive and address key areas of concern: curriculum adaptation, assessment transformation, student engagement, ethical concerns, professional development needs, and pedagogical shifts. Unlike prior studies, which often generalize faculty experiences, this study uniquely captures nuanced faculty strategies and gaps in readiness across a large-scale context in Chinese higher education. Results indicated that faculty members exhibited significant usage of generative artificial intelligence tools both for personal and professional purposes. They also used generative artificial intelligence tools for formative assessment practices, with limited application in summative assessments. Results indicated faculty faced Generative AI tool usage challenges like curriculum adaptation, assessment transformation, student engagement with generative artificial intelligence tools, ethical concerns, professional development, and pedagogical shifts. The findings also demonstrated that faculty members were struggling to address these challenges. Furthermore, outcomes indicated that professional development and ethical concerns directly, indirectly, positively and significantly contribute to helping faculty to enhance student engagement and pedagogical shifts in their teaching practices. Additionally, curriculum adaptation and assessment transformation have also mediated these relationships. These findings contribute novel insights into how professional development can support effective GenAI integration. Implications are offered for faculty development programs, curriculum design policies, and institutional governance in the era of AI-enhanced education.